2019
DOI: 10.3390/ijgi9010013
|View full text |Cite
|
Sign up to set email alerts
|

The Unbalanced Analysis of Economic Urbanization—A Case Study of Typical Cities in China

Abstract: In the process of economic urbanization, because of competition among cities, agglomerations and polarization of regional economies are produced. This paper studies the urban polarization with Chinese characteristics and the regional economic urbanization, which include the imbalance under the influence of different geographical factors between the east and west of China and the imbalance under the comprehensive influence of natural and human factors in the province. The urban economic polarization index (UEPI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Buildings 2023, 13, x FOR PEER REVIEW 15 of 22 events in any region in the process of rapid urbanization. In turn, it exacerbates urban environmental problems and threatens the sustainable development of megalopolises [92,93]. In the coming decades, China's urbanization rate will continue to increase steadily at a rate of about 1% per year [88], and it is firmly believed that urbanization is the only way for the country to modernize.…”
Section: Discussionmentioning
confidence: 99%
“…Buildings 2023, 13, x FOR PEER REVIEW 15 of 22 events in any region in the process of rapid urbanization. In turn, it exacerbates urban environmental problems and threatens the sustainable development of megalopolises [92,93]. In the coming decades, China's urbanization rate will continue to increase steadily at a rate of about 1% per year [88], and it is firmly believed that urbanization is the only way for the country to modernize.…”
Section: Discussionmentioning
confidence: 99%
“…Land use/land cover changes are the result of the interaction between humanity and nature, and they involve complex mechanisms and processes (Ali et al, 2020). Next, the centrality indicators of road proximity, internality, and straightness are extended by considering the node-based weights of the road class and road width (Cao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In a separate study conducted in the United States, researchers used correlation analysis to examine the relationship between regional information-oriented and economic growth. The results of the study showed that there was a positive correlation between regional information-oriented and economic growth, with a correlation coefficient approximately to 0.6, which indicates that as regional informationoriented increases, economic growth also increases [11] .…”
Section: Related Research Introductionmentioning
confidence: 86%